Manajemen Peningkatan Mutu Pendidikan - Willem Mantja (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Management of Educational Quality Improvement. Educational total quality management is the integration of all functions and processes within an educational organization in order to achieve continous improvement of the quality of school outputs and services. The main objective is the satisfaction of the clients or costumers. In the educational or school organization, there are three basic definitions of quality: quality assurance, contract conformance, and costumer driven. The application of TQM in the context of educational organization is based on a framework that educational managers are able to make the process of improvement.